TRENDS IN THE DEVELOPMENT OF ECOTOURISM: AN ANALYSIS OF THE LITERATURE AT A GLOBAL LEVEL | TENDÊNCIAS NO DESENVOLVIMENTO DO ECOTURISMO: UMA ANÁLISE DA LITERATURA - Franco, Antonio Carlos; Franco, Luciane Silva; Maganhotto, Ronaldo Ferreira (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2022)
Ecotourism is the appropriate activity for carrying out tourism in protected places, as it is concerned with environmental conservation, contributing to the development of local communities. The potential for ecotourism is significant due to national parks, wildlife sanctuaries, conservation reserves and community reserves, many of which include animal reserves. Therefore, this study aims to conduct a systematic review of the literature on high impact research on the evolution and trends related to ecotourism in the world context, in order to understand the different perspectives through critical analyzes, identifying gaps for future research and investigating trends in this body of literature. The results show the main developments and trends in the referred body of literature, possible relationship of ecotourism, as well as the main magazines that carried out studies on the topic and what are their results. The main countries that published high impact studies (JCR 2019) on the topics covered and number of citations can be consulted. In addition, this study provides an overview of ecotourism and the possibilities for future research. The development of studies on ecotourism must be related in terms of protected areas, natural resources and sustainable tourism. For future studies, it is considered important to investigate other impacts that influence Ecotourism, such as political, technological and legal. The study provides perspectives on ecotourism around the world in encouraging research in the sector. DOI: 10.18226/23190639.v9n3.04 Antônio Carlos Franco*, UTFPR, Brasil Email: francoancf@hotmail.com Luciane Silva Franco, UNICENTRO, Brasil Email: lu05-franco@hotmail.com Ronaldo Ferreira Maganhotto, UNICENTRO, Brasil Email: rmaganhotto@unicentro.edu.br Submetido: Fevereiro 2021 Aceito: Junho 2021 *Contato para Correspondência